A comprehensive analysis of improving the QoS of IMM traffic for high speed wireless campus network - Yalli, Jameel Shehu; Abdul Latif, Suhaimi; Masud, Mosharrof Hussain; Alam, Md Korshed; Hassan Abdalla Hashim, Aisha (2014)
Interactive Multimedia (IMM) applications such as voice and video conferencing are very important in our learning environment. They offer useful services that benefit its users but these services suffers performance degradation from today’s high speed Wireless Local Area Network (WLAN). However, guaranteed Quality of Service (QoS) remains the bottleneck in the network which becomes a great challenge in attempting to improve its performance. This work reviewed many approaches and considers mapping QoS class parameters such as Quality of Service Class Identifier (QCI), Maximum Bit Rate (MBR) and Allocation and Retention Priority (ARP) to the upstream and downstream data flowing in the network as an attempt to improve its performance. Priority is then given to the QoS bearer packets by associating Differentiated Services Code Point (DSCP). A comprehensive analysis of QoS in different protocols in wireless networks has been studied. Open issues and research directions have been addressed with a proposed mechanism to enhance the QoS of the wireless network